As Casas Familiares Rurais e a continuidade do processo formativo dos alunos egressos - Sinhoratti, Fabiana (2015)
Inside in the line of society, knowledge and Education search in the Education master in UNIOESTE, in Francisco Beltrão/PR Campus, this search is concentrated in the debate around the rural youth and education, which has as the analysis base the example of the Rural Family Houses (Casas Familiares Rurais-CFR s). The study profile is ground in the egress youth from the CFR s in Enéas Marques, Pérola do Oeste and Santo Antonio do Sudoeste. It is possible to conclude that in Paraná state the Rural Family Houses project, although it is managed by a non-governmental organization (Brazil South Rural Family Houses Association-ARCAFAR/SUL), it has received a meaningful support from state government to the dissemination of the teaching purpose based in the Alternation Pedagogy. Following this initial comprehension, the goal is to understand the contribution proportionated to the egress youth in the continuous of the formative process through the educational experience offered in the CFR s. Based in the Dialectical and Historical Materialism theory and methodology, which gives the possibility to do a critical comprehension of the social reality, it was possible to observe some elements that involves the Brazilian countryside, its youth and the education offered in this context. The comprehension of the contradictions that characterize the Brazilian country is the initial element to this search development, due to this comprehension has done the dynamic reading of preexisting conditions to the CFR s projects got a meaningful amplitude. It was possible to realize that the rural youth introduce themselves into the mentioned context as the population parcel is the most injured with the changes happened as in the countryside as in the education. After, it is interesting to understand what the Alternation Pedagogy is, due to it guides the work developed in the CFR s. It is important to remember the previous mentioned project got shape and expressivity in Paraná state during the 90 s decade, a period characterized by a strong influence of educational politics lined in the neoliberal conceptions. So, based in these elements, this search concretize from the data analysis got from School Register State System(SERE) and in the interviews done with egress students in 2011, 2012 and 2013 in respective studied CFR s. Based in these elements there was the possibility to do the critical reading of CFR s proposal and the contribution to the rural young in Francisco Beltrão Regional Educational Center and, in the same time, observe the potentialities as a singular educational proposal.